Restoration of blood brain barrier integrity post neurosurgical resection in drug resistant epilepsy - Campbell, Matthew; Doherty, Colin (My University, 2025)
Surgery for temporal lobe epilepsy (TLE) is a well-recognised therapy for drug resistant seizures which occur in more than 50 % of patients with TLE. Blood-brain barrier (BBB) dysfunction is commonly observed in resected brain tissue from patients with treatment resistant epilepsy however, no studies have documented the recovery of BBB function following surgery. We firstly prospectively performed dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) on seven patients scheduled for temporal lobe resections before and after resection. DCE-MRI revealed BBB dysfunction in frontal and temporal brain regions. At 6–24 months post-resection, there was a reduction in the percentage of brain volume with BBB dysfunction in 5/7 patients. We then retrospectively characterised resected brain tissue from 6 further TLE cases (total n = 13) by q-RT-PCR and immunohisto-chemistry which revealed region-specific changes in markers of BBB integrity and inflammation with changes in CLDN12 and TJP1/2 in the hippocampus and CSF1R pathway genes in cortical and hippocampal tissue. BBB dysfunction is a key component of the molecular disruption caused by seizures and in longstanding early onset chronic epilepsy that is refractory to treatment. Here, we demonstrate for the first time the rescue of BBB dysfunction by controlling seizures after surgery.
PUBLISHED
Cited by: 1
Keywords: Blood-brain barrier; Temporal Lobe Epilepsy; Drug resistant seizures; Dynamic contrast-enhanced MRI